Case Report: Mature congenital teratoma masquerading as orbital cellulitis in a 12-day-old infant - Huelsbeck, Alyssa C.; Froines, Colin P.; van Landingham, Suzanne W. (Frontiers in Ophthalmology, 2025)
BackgroundCongenital orbital teratoma is a rare neoplasm that typically presents as progressive, unilateral proptosis in an otherwise healthy newborn. Management includes prompt surgical excision, with guarded visual prognosis but excellent survival.Case presentationA 12-day-old healthy infant presented with progressive left eye swelling and proptosis. She was initially diagnosed with orbital cellulitis and treated with IV antibiotics. Magnetic resonance imaging (MRI) showed a 1.5x1.9x2.1 cm left intraconal mass with 9mm of proptosis and significant mass effect. The patient underwent left lateral orbitotomy for biopsy and excision of the mass. Histopathologic examination showed neutrophilic inflammation and granulation tissue with foci of gastrointestinal epithelium, cartilage, squamous epithelium, and ganglion cells, consistent with mature congenital teratoma. The postoperative course was uncomplicated and there is no sign of recurrence at 21 months of age.ConclusionOrbital teratoma should be suspected in a rapidly growing orbital mass in a newborn. Imaging showing characteristic findings should lead to prompt excisional biopsy. Tumor markers can be used to monitor for recurrence, which is rare.